Sockets, shellcode, porting & coding : reverse engineering exploits and tool coding for security professionals - Foster, James C. (Syngress Pub. ; Distributed by O'Reilly Media in the United States and Canada, 2005)
Covers in detail the five most important disciplines for security professionals and software developers: coding, sockets, shellocode, porting applications, and coding security tools.